(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article aims to establish relationships between fashion, memory and the museum, with a view to understanding the phenomenon of fashion that leaves the commonplace and enters the museum spaces. Thus, we are dedicated to examining how fashion and the museum, as fields of cultural production, are structured. The theoretical framework comprises the following authors: Le Goof (2013), Nora (1993), Crane (2008), Lipovetsky (2009), Sant’Anna (2010), Norogrando (2015), Andrade (2008). This work was developed from the result of exploratory research adopting the following methodological steps: literature review, documentary research and case studies that guided the analyzes and syntheses presented.